Remixing the plague of images: video art from Latin America in a transnational context - Vergara-Vargas, Erandy (My University, 2015)
There has been a strong production of video art in Latin American countries in the last four decades, and an equally strong tradition of appropriation and remixing pre-recorded materials, particularly images from popular culture. Remix in video art encompasses reusing, recycling, referencing, and redirecting audio-visual materials towards orientations distinct from the original source. Since the raw materials of many video remixes include imagery that comes from advertising, cinema, magazines and television, apart from formal experimentation, critiques to those systems of representation are common and bold. The aim of numerous artists is to re-evaluate the elements constituting visual culture and to articulate resistance to hegemonic images and discourses in a transnational context. In contemporary video art from Latin America there is a significant body of work dealing with questions of memory mixing past and present. Other pieces connected to the lineage of the avant-garde in Latin America explore questions of modernity through citations and remix. This chapter focuses on four videos deploying remix strategies as metacommentaries on remix itself. As I explain, such works cannot be separated from the troubling genesis of the source materials and the wider context of circulation and reception, yet at the same time they function on various levels as self-reflexive cases of the practice of remix. Concretely, this chapter focuses on four case studies which use remix to revise the smooth flowing or the unsteady flickering of the plague of images circulating online and offline on a daily basis. There is the bitter criticism of transnational capitalism and diverse forms of invasion in Ximena Cuevas’ Cinepolis (2003); the appropriation of images about protection and surveillance in Graciela Fuentes’ To Protect (2003); the re-vision of fifteen years of Colombian television in José Alejandro Restrepo’s Viacrucis (2004); and the scratching of a speech by Fidel Castro in José Toirac’s Opus (2005). Despite their differences, these artists complicate remix as a contemporary aesthetics in works privileging contrast and noise to draw attention to the smoothness and/or fragmentation of mainstream media, to re-orient the reading of known sounds and images, as well as to expose the relationship between the appropriated elements and what Slavoj Žižek calls the “material traces of ideology.”
Keywords: video art; Latin America; remix; media studies